Application of in vitro release testing (IVRT) to assess "sameness" /differences of topical clotrimazole formulations - Wellington, Hannah Margaret Mary (Rhodes University, Faculty of Pharmacy, Pharmacy)
Embargoed. Possible release date early 2025 pending publications.
Keywords: Uncatalogued